Changes in dentofacial vertical dimension with class I before and after treatment orthodontic appliance with and without extractions of first four premolar teeth - Octavianti, Fitri; Salim, Jono; Thahar, Bergman; Mardiati, Endah (Padjadjaran Journal of Dentistry, 2010)
Introduction: There are different opinions on the effect of extraction on the first four premolar teeth. The purpose of this study is to analyzed change of dentofacial vertical dimension before and after orthodontic treatment for two groups of patients treated with and without extractions of first four premolar teeth. Methods: A method by Sivakumar and Valiathan (2008) using lateral cephalometry on 20 extraction cases and 15 cases of non-extraction was employed. Tracing was conducted before and after orthodontic treatment and some 13 measurements were conducted manually using a protractor, i.e. mandibular plane angle, anterior facial height, lower anterior facial height, posterior facial height, facial height index, FH-U1, FH-U6, FL -L1, FL-L6, Svertical-U1, Svertical-U6, Pogvertical-L1-L6 Pogvertical. Statistical analysis using t-test with P> 0.05 for paired, Showed that there was no significant changes in dentofacial vertical dimension for malocclusion Class I cases before and after treatment for samples treated with and without extraction of the first four premolar teeth for both groups of samples. Results: No significant difference found in the dentofacial vertical dimension for the extraction and non-extraction groups of samples. Conclusion: orthodontic treatment for class I malocclusion cases, both with and without extraction, did not cause any significant difference in the dentofacial vertical dimension. Showed that there was no significant changes in dentofacial vertical dimension for class I malocclusion cases before and after treatment for samples treated with and without extraction of the first four premolar teeth for both groups of samples. Results: No significant difference found in the dentofacial vertical dimension for the extraction and non-extraction groups of samples. No significant difference found in the dentofacial vertical dimension for the extraction and non-extraction groups of samples. Conclusion: There are no changes in the vertical dimension of dentofacial before and after treatment in Class I with a retraction and extraction four first premolars fixed orthodontic appliance.